2008
DOI: 10.3748/wjg.14.108
|View full text |Cite
|
Sign up to set email alerts
|

Expression of phosphatase and tensin homolog deleted on chromosome ten in liver of athymic mice with hepatocellular carcinoma and the effect of Fuzheng Jiedu Decoction

Abstract: AIM:To explore the expression of phosphatase and tensin homolog deleted on chromosome ten (PTEN) in liver of athymic mice with hepatocellular carcinoma (HCC) and the effect of Fuzheng Jiedu Decoction (FJD). METHODS:Forty eight male BALB/c athymic mice models were built by Bel-7402 with an indirect method. After 24 h of postoperation, the 48 athymic mice were distributed randomly into 4 groups: A, B, C, D, each group had 12 athymic mice. Group A were treated by intragastric administration with FT207 (Tegafur) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…According to the theory of traditional Chinese medicine, JPJD exerts certain effects, including enhancement of the absorption and transportation of nutrient substances and an antitumor effect ( 2 ). However, previous studies have indicated that JPJD can effectively promote quality of life and survival time, but is not able to directly inhibit tumor growth ( 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the theory of traditional Chinese medicine, JPJD exerts certain effects, including enhancement of the absorption and transportation of nutrient substances and an antitumor effect ( 2 ). However, previous studies have indicated that JPJD can effectively promote quality of life and survival time, but is not able to directly inhibit tumor growth ( 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the theory of traditional Chinese medicine, JPJD exerts certain effects, including enhancement of the absorption and transportation of nutrient substances and an antitumor effect ( 2 ). However, previous studies have indicated that JPJD can effectively promote quality of life and survival time, but is not able to directly inhibit tumor growth ( 2 , 3 ). Therefore, a hepatocellular carcinoma model based on food restriction combined with laxative (FRL) administration was established in the present study in order to investigate the immunological mechanism underlying the potential anti-hepatoma effects of JPJD with TCRVβCDR3 as the suggested target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that CC may affect >80% of patients with cancer, which directly affects the overall survival and the life quality of the patients, reduces the tolerance to radiotherapy and chemotherapy, and increases the occurrence rate of complications, thus CC is regarded as an crucial cause of death in patients with cancer ( 3 , 4 ). The pathogenesis of CC remains complex, and there is little information regarding the use of therapeutic strategies including anti-inflammatories, appetite stimulation and nutritional support, which may aid in the prevention of skeletal muscle degeneration, however further investigation is required ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies [ 18 ] revealed that OATP2A1 played a pivotal role in the development of liver cancer. The general status of liver cancer patients was improved by [ 19 ] Jianpijiedu decoction (JPJD). However, further research is needed to determine whether JPJD positively impacts the liver microenvironment during liver cancer by regulating the levels of OATP1B2 or ABCC2.…”
Section: Introductionmentioning
confidence: 99%